Producing - Lewis, Jon, 1955- (Book collections on Project MUSE., 2015)
""Six insightful critics turn their collective gaze to Hollywood's least-gratifying field of endeavor and redefine the writer's role in film history. A witty, instructive, and long overdue survey.""